Green synthesis of a Se/HPCF–rGO composite for Li–Se batteries with excellent long-term cycling performance. Issue 44 (2nd November 2017) - Zeng, Lingxing; Chen, Xi; Liu, Renpin; Lin, Liangxu; Zheng, Cheng; Xu, Lihong; Luo, Fenqiang; Qian, Qingrong; Chen, Qinghua; Wei, Mingdeng
Abstract : A Se/HPCF–rGO composite was synthesized as a highly stable cathode material for Li–Se batteries. Abstract : In the present work, we designed a dual-spatial carbon protection strategy for a Se reservoir, in which a Se/hierarchical porous carbon fiber (Se/HPCF) composite was homogeneously anchored on reduced graphene oxide (Se/HPCF–rGO). HPCF with high specific surface area and large pore volume was synthesized for the first time by using sodium lignosulfonate (LN) as a green porogen based on an electrospinning route. The Se/HPCF–rGO composite exhibits excellent electrochemical performance when employed as a cathode material for Li–Se batteries. For instance, a high reversible capacity of 616 mA h g −1 was maintained after 50 cycles at a rate of 0.2C. More importantly, the Se/HPCF–rGO composite delivered a high capacity of 208 mA h g −1 at a high rate of 10C even after 5000 cycles. The outstanding electrochemical performance can be attributed to the synergistic effect of the diverse structural features and fast reaction kinetics for lithium storage.